Optimizing the Utilization of Game-Based Learning Application for Elementary Students First Phase - Sri Sukasmi; Asrowi Asrowi; Nur Arifah Drajati (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Smartphone was a technology-based device that was almost used and owned by every individual, both teachers and students. This study aimed to identify opportunities for using smartphones to support learning activities. This type of research was included in qualitative research, the research subject consists of 30 students of primary education level who were randomly selected. The data collection method used was a survey with a research instrument, namely a questionnaire. Through the questionnaire, it was found that 86.7 percent of students have smartphones that are used to play games (76.7 percent), using smartphones in a day for more than 5 hours (63.3 percent) this was certainly an opportunity for innovative learning media to emerge. with a game format (game-based learning). Referring to the results, it could be concluded that the innovation of learning media with game-based learning has a very big opportunity to be used by teachers to support the learning process.